Unspoken Criticism: Audiovisual Forms of Critique as Fair Use - Fisher, Alec (The Columbia Journal of Law & the Arts, 2021)
Imagine a short video from a film critic highlighting the latest superhero summer blockbuster. First, we see a few seconds of the big action finale from the copyrighted film. The superhero flies through the air, zipping between skyscrapers at breakneck speed. The video cuts to a clip of the critic, in closeup, yawning for several seconds. Then, it cuts back to the film, and we see the superhero engaged in the film’s climactic battle, pummeling the villain with superhuman strength. Next, it cuts back to the critic, who is now asleep and snoring loudly. The video ends. Is the resulting video a work of criticism? It may depend on whom you ask. For a court assessing criticism for fair use purposes, the answer is currently unclear. In recent years, the rise of online social media platforms and increased access to the tools of creative expression—smartphone cameras, and photo and video editing software, to name a few—have led to the proliferation of audiovisual criticism on the internet. Online audiovisual criticism is now so ubiquitous that numerous YouTube channels dedicated to film and television criticism boast viewership in the hundreds of millions. Yet, as new technologies have lowered the barriers to entry for creators of works of criticism, these technologies have also fostered a creative evolution of criticism in ways that present novel questions for copyright law. On YouTube and other video sharing sites, reaction videos have become a popular form of audiovisual criticism. Reaction videos are online videos that contain, quite simply, “footage of people reacting to things.” Reaction videos traditionally include footage of the video participant intercut with or superimposed over the pre-existing, and often copyrighted, video footage to which they are reacting. This reaction is frequently extemporaneous, though it need not be, and it may or may not include other graphical, visual, or audio elements that lend emphasis and context to the participant’s commentary. Because reaction videos utilize film-specific conventions and techniques to enhance their commentary, reaction videos sometimes criticize the underlying copyrighted work in a non-spoken, visual manner. Criticism is a classic form of fair use—an affirmative defense to copyright infringement. However, the traditional analysis for fair use criticism has focused heavily on a work’s text or dialogue, with less emphasis placed on a work’s non-textual or non-spoken elements. As reaction videos and other forms of online audiovisual criticism rise in popularity, courts assessing these videos as works of criticism for fair use purposes have struggled to apply the traditional fair use framework to these types of online criticism. This Note argues that the traditional legal framework for analyzing a work of alleged criticism as fair use is particularly constraining for YouTube reaction videos and other audiovisual forms of criticism that largely critique or comment on an original work in a non-spoken, visual manner. It discusses the emphasis that the current fair use jurisprudence places on spoken and written critical elements when undertaking a fair use analysis of a work of criticism, then advocates for a new conception of fair use criticism that incorporates film-specific analytical techniques and concepts when analyzing the critical elements of online audiovisual works. Part I discusses the statutory codification of the fair use doctrine in copyright law and how the doctrine has been shaped through the years by subsequent judicial interpretation. Part I also discusses the history of YouTube reaction videos as a unique audiovisual format. Part II explores the ways in which courts have recently applied the fair use doctrine to alleged works of audiovisual criticism and the emphasis courts place on spoken and written critical elements. Part III argues that courts assessing online audiovisual works as alleged works of criticism should incorporate analytical tools and interpretive theories commonly utilized in film studies contexts—including an analysis of editing, shot composition, and camera movement—when parsing alleged works of audiovisual criticism for transformativeness under factor one of the fair use test. Finally, Part IV uses a recently decided fair use case out of the Southern District of New York as a real-life example to explore how a court could apply film-specific analytical tools to more accurately identify and assess the critical elements of a work of audiovisual criticism for fair use purposes.